The role of prosody in non-verbal communication - Lukianenko, N.; Лук’яненко, Наталія Миколаївна (Харківський національний автомобільно-дорожній університет, 2024)
This article examines the critical role of prosody in non-verbal communication, focusing on its impact on emotional expression and interpersonal interactions. Prosody encompasses elements such as pitch, rhythm, and intonation, which collectively convey meaning beyond the literal content of speech. Through a comprehensive review of existing literature and empirical investigations, this study highlights how variations in prosodic features influence the interpretation of messages in diverse contexts. The findings demonstrate that prosody is essential for conveying emotions, clarifying intentions, and enhancing social connections among speakers. Additionally, the research underscores the importance of considering cultural differences in prosodic interpretation, revealing that listeners’ backgrounds can significantly shape their understanding of emotional tones. The article concludes by suggesting future research avenues to further explore the nuances of prosodic communication across different languages and settings, emphasizing the need for interdisciplinary approaches to deepen our understanding of this complex aspect of human interaction.
Функція просодії у невербальному спілкуванні
Keywords: prosody; non-verbal communication; intonation; emotional expression; interpersonal interaction; cultural context; просодія; невербальне спілкування; інтонація; емоційний вираз; міжособистісна взаємодія; культурний контекст; 81'3:316.77; 10.30977/BUL.2219-5548.2024.107.0.167